Between customs and landscape: Ralph Harland Cake’s fund photographic memory - Castelli Olvera, Sarahi Isuki; Vázquez Valdés, Verónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In this work we sustain that the album Memoria fotográfica del Fondo Ralph Harland Cake, presents views that take up the visual culture of the costumbrismo through the landscape and the places that highlight the economic dimension of the territory. The method of analysis consists in a formal analysis, the identification of the iconographic and historical referents of the source, and the interpretive theoretical analysis of sociocultural processes. We conclude that this album is structured from photographs that follow the tradition of the romantic costumbrismo. These scenes are built from two types of landscape: natural and built.